THE PRACTICE OF ALTERNATIVE ASSESSMENT METHODS IN ISLAMIC EDUCATION AND THE MOTIVATION AMONG SECONDARY SCHOOL STUDENTS IN ABU DHABI - Kasasbeh, Nabeeh Abd Almahdy; Bin Jamil, Asyraf Isyraqi; Bin Yussuf, Ahmad (Journal of Islamic Educational Research, 2023)
COVID-19 pandemic invaded the world and formed a social isolation in all aspects of life, including the educational institutions. This affected the face-to-face communication between teachers and the students, which resulted in a decrease in students’ motivation towards learning and achievement. Therefore, the study aimed to investigate if there is a correlation between the alternative assessment methods practices in Islamic education and the level motivation the secondary schools’ students in the emirate of Abu Dhabi. The study sample consisted of (385) male and female secondary school students in Al Ain City, the research used the descriptive correlative analytical approach in this study, and to achieve the objectives of this study, the researchers prepared a questionnaire to measure the alternative assessment and he used both the motivation to measure that, and they were validated. A set of results was achieved, the most important of which is: there is a statistically significant correlation between the practice of the alternative assessment method in Islamic education and the level of motivation. In addition, the research results also showed that there are no statistically significant differences, due to the gender and grade variables, in teachers’ use of the alternative assessment methods.